Study of the relationship between the Internet and SMS addiction with the motivation of educational development and students’ spiritual (mental) intelligence - Mirzaei, Parvin (International Journal of Psychosocial Rehabilitation, 2020)
The present study examines the relationship between the Internet and SMS addiction and the motivation for educational development and spiritual (mental) intelligence among students. For this purpose among the students who studied in the second level of high school in Tehran during the academic year of 2016-2017, 180 people were selected randomly. The data gathering tool in this research is a standard questionnaire of the Internet and SMS addiction, spiritual intelligence, and educational motivation. The present research is a descriptive design of correlation type. Data were analyzed using SPSS software version 19 using regression, Pearson correlation coefficient and t-test. According to the results of this study, spiritual intelligence was a strong predictor of addictive behaviors such as Internet addiction. The results indicated that the Internet addicts had significantly lower levels of spiritual intelligence than other subjects. However, in the present study among the students, gender was not effective. Also, the present study showed that there is a meaningful relationship between spiritual intelligence and the motivation for educational development (sig> 0.05). Although the relationship between spiritual intelligence and internal motivation and development is positive, the relationship between spiritual intelligence and impulsivity is negative. So, there is a significant relationship between educational motivation and internet addiction.